Fiqh of priorities in the light of the purposes of sharee'ah - El-Seoudi, Abdel Wadoud Moustafa Moursi; Mohd Nor, Amir Husin; Muhammad Husni, Ahmad; Omar, Anwar Fakhri; Laluddin, Hayatullah; Ibrahim, Ibnor Azli; Samsudin, Muhammad Adib; Alias, Muhammad Nazir (Medwell Journal, 2012)
This research tries to answer the question that reads: What is meant by the Fiqh of Priorities? What is the relationship between it and the other religious basic principles? How can we make benefit of it in confronting our contemporary problems? What is meant by the Fiqh of Priorities and what is its relationship with the other usool (religious basic principles)? Fiqh of Priorities means the most appropriate way of understanding the rulings that are in conformity with the objectives of the religion through achieving the most important and beneficial benefits, warding off the evils or the lesser harm of them, as well as observing the results that may be caused by these rulings. It is a kind of understanding which is followed by the Fiqh of Reality in its different aspects and the Fiqh of Text through knowing its aims and objectives so that the jurisprudence scholars may choose the most appropriate in time and result. Therefore, this kind of Fiqh is related to three other matters that should be understood so that the meaning of the Fiqh of Priorities may be clear for us, the thing that will make us care about it and apply it in the real life of our nation. The first is the objectives of the Sharee‘ah (Revealed laws of Islam). The second is removing difficulty and hardship. The third is elimination of means that may lead to unfavorable results. In this brief research, researchers will touch upon them according to the same earlier mentioned order.